Ballistic evaluation and damage characterization of 3‐D printed, alumina‐based ceramics for light armor applications. Issue 2 (11th December 2019) - Jones, Tyrone L.; Vargas‐Gonzalez, Lionel R.; Scott, Brian; Goodman, Bill; Becker, Benjamin
Abstract: The goal of this work was to present results of mechanical characterization and ballistic investigation of 3‐D printed alumina (Al2 O3 )‐based armor plates, manufactured using two additive manufacturing‐based methods: pressurized spray deposition (PSD) and direct ink write (DIW), to determine the maturity of these additive‐based processes against the industry standard process. The DIW plates exhibited superior hardness, flexural strength, and density compared to the PSD plates, and in many respects, even eclipsed some of the properties of the commercial isopressed (IP) material. Plates (90 mm × 90 mm × 8 mm) of these composition were manufactured for ballistic analysis in accordance with established ballistic characterization procedures, using a 50.8‐mm‐thick Aluminum 6061 plate as backing and witness plates in the case of penetration or deformation. Six alumina plates were examined ballisitically (one shot per plate) against the 12.7 mm APM2 projectile (45.9 g) at an impact velocity of 840 m/second. The plates that were manufactured using the DIW method provided a higher impact resistance than the PSD method, however, both did not perform as well as the traditionally processed IP material, due to the presence of defects introduced due to the printing processes.